The effect of Kinesio Tape on scapular kinematics with different external loads in healthy subjects - Dhein, William; Chaves, Alisson de Carvalho; Momo, Júlia Araújo; Flores, Natália Miranda; de Toledo, Joelly Mahnic; Mocellin, Matheus Pitrez da Silva; Loss, Jefferson Fagundes (Manual Therapy, Posturology & Rehabilitation Journal, 2021)
The purpose of the study was to investigate the effects of Kinesio Tape (KT) on scapular kinematics with different external loads in healthy subjects. Twenty-three subjects performed abduction, scaption and flexion of their shoulders in three conditions: (1) no load (2) dumbbell and (3) elastic band resistance. KT was applied (I-shaped) over the upper trapezius muscle, and scapula kinematic data was captured and analyzed based on Euler angles. The situations and interactions of the different loads and KT were compared using a repeated measures two-way ANOVA. KT decreased the upward rotation during the movements of abduction, scaption and flexion of the shoulder. There was an effect of load in all evaluated movements, but there was no interaction between the load and the KT. It can be concluded that KT and load showed effects on scapula kinematics. Regardless of the load condition (no load, dumbbell or elastic resistance), the effects of the KT on scapula kinematics will be the same in healthy subjects.